2015
DOI: 10.1002/per.1984
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Self–Esteem in Partner Relationships

Abstract: Previous research on the role of self-esteem in partner relationships indicates that it is both predictive of and predicted by variables such as relationship satisfaction. However, most of these studies were constrained to only relationship satisfaction, cross-sectional or individual data. In the present study, we examine the dynamic interplay between self-esteem and both broad (i.e. relationship satisfaction) and specific aspects of relationship quality (independence and connectedness) reflecting the fulfilme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 73 publications
8
84
0
Order By: Relevance
“…The results found for loneliness additionally correspond to findings regarding the role of social relationships in personality development (Lehnart & Neyer, ; Mund, Finn, Hagemeyer, Zimmermann, & Neyer, ; Mund & Neyer, ; Robins, Caspi, & Moffitt, ). Broadly speaking, those studies found that experiences in self‐selected, intimate relationships exert influences on personality development.…”
Section: Discussionsupporting
confidence: 84%
“…The results found for loneliness additionally correspond to findings regarding the role of social relationships in personality development (Lehnart & Neyer, ; Mund, Finn, Hagemeyer, Zimmermann, & Neyer, ; Mund & Neyer, ; Robins, Caspi, & Moffitt, ). Broadly speaking, those studies found that experiences in self‐selected, intimate relationships exert influences on personality development.…”
Section: Discussionsupporting
confidence: 84%
“…In line with previous research (e.g. Davila et al, 1999;Mund et al, 2015;Neyer & Asendorpf, 2001;Robins et al, 2002), we found that a lower level of relationship satisfaction was linked to an increase in the target's avoidant attachment and to an increase in the partner's anxious attachment across 6 months. Again, it was contrary to our prediction that we found no significant effects for neuroticism and low self-esteem.…”
Section: Socialization Effectssupporting
confidence: 92%
“…In two other studies that used five waves of data spread over 12-years (Orth et al, 2012) and two waves of data with a four-year time interval (Neyer & Asendorpf, 2001), self-esteem predicted change in relationship quality, whereas relationship quality did not predict change in self-esteem in young adulthood. In addition, Mund, Finn, Hagemeyer, and Zimmermann (2015) found that self-esteem and relationship satisfaction were dynamically intertwined in two multiwave longitudinal datasets of adults. Within the first dataset consisting of young adults that were followed for 15 years across four waves, change in self-esteem and change relationship satisfaction were positively linked across all assessments.…”
Section: The Interplay Between Self-esteem and Relationship Satisfactionmentioning
confidence: 99%